Cell therapies in the clinic. Issue 2 (26th February 2021) - Wang, Lily Li‐Wen; Janes, Morgan E.; Kumbhojkar, Ninad; Kapate, Neha; Clegg, John R.; Prakash, Supriya; Heavey, Mairead K.; Zhao, Zongmin; Anselmo, Aaron C.; Mitragotri, Samir
Abstract: Cell therapies have emerged as a promising therapeutic modality with the potential to treat and even cure a diverse array of diseases. Cell therapies offer unique clinical and therapeutic advantages over conventional small molecules and the growing number of biologics. Particularly, living cells can simultaneously and dynamically perform complex biological functions in ways that conventional drugs cannot; cell therapies have expanded the spectrum of available therapeutic options to include key cellular functions and processes. As such, cell therapies are currently one of the most investigated therapeutic modalities in both preclinical and clinical settings, with many products having been approved and many more under active clinical investigation. Here, we highlight the diversity and key advantages of cell therapies and discuss their current clinical advances. In particular, we review 28 globally approved cell therapy products and their clinical use. We also analyze >1700 current active clinical trials of cell therapies, with an emphasis on discussing their therapeutic applications. Finally, we critically discuss the major biological, manufacturing, and regulatory challenges associated with the clinical translation of cell therapies.